Increased TGFβ1 and SMAD3 Contribute to Age-Related Aortic Valve Calcification - Chakrabarti, Mrinmay; Bhattacharya, Aniket; Gebere, Mengistu G.; Johnson, John; Ayub, Zeeshan A.; Chatzistamou, Ioulia; Vyavahare, Narendra R.; Azhar, Mohamad (Frontiers in Cardiovascular Medicine, 2022)
Aims: Calcific aortic valve disease (CAVD) is a progressive heart disease which is particularly prevalent in elderly patients. The current treatment of CAVD is surgical valve replacement, but this is not a permanent solution, and it is very challenging for elderly patients. Thus, a pharmacological intervention of CAVD may be beneficial. In this study, we intended to rescue aortic valve (AV) calcification through inhibition of TGFβ1 and SMAD3 signaling pathways. Methods and results: The klotho gene, which was discovered as an aging-suppressor gene, has been observed to play a crucial role in the AV calcification. The klotho knockout (Kl-/-) mice have shorter life span (8-12 weeks) and develop severe AV calcification. Here, we showed that increased TGFβ1 and TGFβ-dependent SMAD3 signaling were associated with AV calcification in Kl-/- mice. Next, we generated Tgfb1- and Smad3-haploinsufficient Kl-/- mice to determine the contribution of TGFβ1 and SMAD3 to the AV calcification in Kl-/- mice. Histological and morphometric evaluation suggested significant reduction of AV calcification in Kl-/-;Tgfb1+/- mice compared to Kl-/- mice. Smad3 heterozygous deletion was observed to be more potent in reducing AV calcification in Kl-/- mice compared to the Kl-/-;Tgfb1+/- mice. We observed significant inhibition of Tgfb1, Pai1, Bmp2, Alk2, Spp1, and Runx2 mRNA expression in Kl-/-;Tgfb1+/- and Kl-/-;Smad3+/- mice compared to Kl-/- mice. Western blot analysis confirmed the inhibition of TGFβ canonical and non-canonical signaling pathways was associated with the rescue of AV calcification of both Kl-/-;Tgfb1+/- and Kl-/-;Smad3+/- mice. Conclusion: Overall, inhibition of TGFβ1-dependent SMAD3 signaling pathway significantly blocks the development of AV calcification in Kl-/- mice. This information is useful in understanding the signaling mechanisms involved in CAVD.